A Gaia data release 2 catalogue of white dwarfs and a comparison with SDSS - Gentile Fusillo, Nicola Pietro; Jordan, Stefan (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We present a catalogue of white dwarf candidates selected from the second data release of Gaia (DR2). We used a sample of spectroscopically confirmed